Cataract Surgical Rate between 2006 and 2010 in Tehran Province - Hassan HASHEMI; Mehdi KHABAZKHOOB; Farhad REZVAN; Koroush ETEMAD; Hamidreza GILASI; Soheila ASGARI; Alireza MAHDAVI; Sara SOROUSH; Abbasali YEKTA; Akbar FOTOUHI (Tehran University of Medical Sciences, 2015)
Background: Considering population aging in Iran and the importance of cataract surgery in the old age, this study was performed to show the cataract surgical rate (CSR) between 2006 and 2010 in Tehran Province. Methods: Eighteen centers were randomly selected from cataract surgery centers in Tehran. In each center, one week in every season was randomly selected and the number of cataract surgeries in the week was calculated. In total, 20 weeks were selected in each center in five years. Results: The CSR increased linearly from 8011 cases per 1,000,000 population in 2006 to 12465 cases per 1,000,000 population in 2010. As for patients below 40 years of age, the percentage of the male patients was more while after the age of 40 years, the percentage of the female patients was more in all age groups. At least 96.2% of the surgeries in each year were performed using the phacoemulsification method. From 2006 to 2010, the percentage of outpatient surgery increased from 48.7% to 72.5%. On the other hand, hospitalization for one night or more had a decreasing trend from 2006 to 2010. Conclusion: During 2006-2010, the CSR was acceptable in Tehran in comparison with other studies. However, attention should be paid to the increase in the population of the elderly people. Although more than 95% of the surgeries in the Province of Tehran are performed using the phacoemulsification method, the rate should increase to 100% in the eligible cases.